DOI: 10.11606/d.11.2005.tde-26042005-155246
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho do milho consorciado com diferentes espécies de braquiárias, em Piracicaba, SP.

Abstract: Aos meus avós, pelo carinho e ensinamentos ao longo da vida. Aos meus pais, Takeo e Olinda, pelo apoio e amor oferecido ao longo de minha vida. Ofereço, Aos meus irmãos, Anderson e Gilsem, pelo incentivo. Aos meus tios, por todo carinho.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
7

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
3
2
0
7
Order By: Relevance
“…The absence of interference by forage on corn may be due to the relatively wide distance (0.90 m) between the corn rows, which separated the forage from the corn by 0.45 m. This distance may have reduced early-season competition for water and nutrients between forage species and corn. These results are similar to those obtained by Tsumanuma (2004), who researched corn intercropped with marandu and ruzi grass, and by Borghi & Crusciol (2007), who researched corn intercropped with marandu, in São Paulo state, Brazil. Similarly, Heinrichs et al (2005) found that corn grain yield was not affected by intercropping with green manure species in the first year; in the second year, however, corn grain yield was highest when corn was intercropped with the legumes sunn hemp and pigeon pea.…”
Section: Crop Yield In the First Late-season Plantingsupporting
confidence: 90%
See 1 more Smart Citation
“…The absence of interference by forage on corn may be due to the relatively wide distance (0.90 m) between the corn rows, which separated the forage from the corn by 0.45 m. This distance may have reduced early-season competition for water and nutrients between forage species and corn. These results are similar to those obtained by Tsumanuma (2004), who researched corn intercropped with marandu and ruzi grass, and by Borghi & Crusciol (2007), who researched corn intercropped with marandu, in São Paulo state, Brazil. Similarly, Heinrichs et al (2005) found that corn grain yield was not affected by intercropping with green manure species in the first year; in the second year, however, corn grain yield was highest when corn was intercropped with the legumes sunn hemp and pigeon pea.…”
Section: Crop Yield In the First Late-season Plantingsupporting
confidence: 90%
“…The negative effect of forage plants on corn yield could result from the species or seeding rate of the intercrop (Blaser et al, 2007), or from insufficient rainfall during the late-season to support the growth of both crops (Wilkinson et al, 1987). Other researchers, however, detected no competition between corn with forage plants when forages were grown at low plant densitty in rows between corn (Tsumanuma, 2004;Freitas et al, 2005;Torres et al, 2008). The negative effects on corn caused by competition with the intercropped forage can be minimized through the use of herbicides (Freitas et al, 2005) and shading of the forage species by corn, which is enhanced by corn hybrids with expanded leaf architecture and greater leaf area (Torres et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Tsumanuma (2004) when studying the combination of three species of brachiarias (Brachiaria decumbens, Brachiaria brizantha and Brachiaria ruziziensis) being sown in two seasons (V0 and V4 stage of the maize). No statistical difference were found between treatments for the following variables: Plant height; leaf area index; diameter of the stem; leaf analysis; number of grain rows; number of grains per ear; 1000 grains weight and productivity.…”
Section: Resultssupporting
confidence: 81%
“…Therefore, the later was the sowing of brachiaria, the lower was the production and such results corroborate Tsumanuma (2004), pointing out that late sowing affects in a bad way the initial development and the accumulation of dry matter by brachiaria, caused by water competition rate, nutrients and light, in which maize has high efficiency.…”
Section: 5supporting
confidence: 65%
“…O diâmetro do colmo apresenta correlação com o rendimento, por se tratar de um órgão de reserva da planta (CRUZ et al, 2008), que serão utilizados posteriormente na formação dos grãos. Segundo Tsumanuma (2004), o diâmetro do colmo é uma estrutura destinada ao armazenamento de sólidos solúveis para situações emergenciais, e quanto maior for seu diâmetro, maior será sua capacidade de armazenamento de fotoassimilados, contribuindo consideravelmente para a formação de grãos. No trabalho, os híbridos não manifestaram indicativos que permitissem observar os melhores neste componente de produção.…”
Section: Resultsunclassified